Optimizacija konstrukcije okvira za terensko tovorno vozilo - Harl, Boštjan (Strojniški vestnik, 2001)
We present an approach for the optimum design of a frame for an off- road truck. The objective was to minimize the weight of an existing frame. The stiffness of the frame had to remain approximately the same, while the cross-sectional parameters could be varied in some specified range in order to minimize the weight. Multiple load cases were taken into account simultaneosly in order to consider different loading situations. The design problem was formulated in the form of a standard problem of mathematical programming. This problem was then solved using a gradient-based approximation method. The frame of the truck was discretized by employing highly accurate beam finite elements.
Keywords: vozila terenska; okviri vozil; optimiranje konstrukcij; primeri obremenitveni; tovorna vozila; okvirji; konstrukcije; optimiranje